The role of household modality style in first and last mile travel mode choice. (April 2022) - Lu, Ying; Prato, Carlo G.; Sipe, Neil; Kimpton, Anthony; Corcoran, Jonathan
Highlights: Intra-household interactions are captured in first and last mile travel mode choice. This article reflects heterogeneity of group decision-making. Car-oriented households have more young children and cars. Households with fewer young children are likely to adopt walking for joint travel. Abstract: In the context of public transport, the first and last mile (FLM) travel refers to access to or egress from public transport stations. The poor connection between trip origins and destinations impedes the transition towards sustainable transport by requiring commuters to initially use their cars to travel the FLM. Existing literature identifies that the built and natural environment characteristics influence the travel mode choice for FLM travel. However, this literature has yet to consider how individual FLM travel mode choices are influenced by other household members, i.e., intra-household interactions. Here, this study draws on the notion of household modality style (i.e., reflecting heterogeneity in group decision-making) to account for intra-household interactions in FLM travel mode choice. For broadening the understanding of intra-household interactions, the decision of joint travel is also considered in the current study when understanding FLM travel mode choice. By defining the latent class structure at the household level using a household travel survey for Brisbane, Australia, the latent class nested logit models identify two household modality styles: (1) car-oriented; and (2) multimodal. When considering the decision of joint travel, each household modality style group has a specific preference towards FLM travel time, public transport accessibility, station density, and road network intersection density. These findings provide evidence for policymakers aiming to develop transport integration policies targeting specific household types. The results also have implications in practice through prioritisations of distinct household modality styles more likely to shift towards sustainable transport modes.